Genome-Wide Association Study of Birth Wool Length, Birth Weight, and Head Color in Chinese Tan Sheep Through Whole-Genome Re-Sequencing - Lina Ma; Wei Zhao; Qing Ma; Jin Wang; Zhengwei Zhao; Juan Zhang; Yaling Gu (Animals)
The Chinese Tan sheep is a unique breed of sheep that is typical throughout China, mainly used for fur and meat production. They are widely distributed in northwestern China and are famous for their lambskin and shiny white curly wool. In this study, the phenotypic traits of wool length, birth weight, and head coat color were evaluated in 256 Chinese Tan sheep breeds. Whole genome sequencing generated 23.67 million high-quality SNPs for genome-wide association studies (GWAS). We identified 208 significant SNPs associated with birth wool length, implicating RAD50, MACROD2, SAMD5, SASH1, and SPTLC3 as potential candidate genes for this trait. For birth weight, 1056 significant SNPs, with 76.89% of them located on chromosome 2, were identified by GWAS, and XPA, INVS, LOC121818504, GABBR2, LOC101114941, and LOC106990096 were identified as potential candidate genes for birth weight. The GWAS for head coat color identified 1424 significant SNPs across three chromosomes, with 99.65% on chromosome 14, and SPIRE2, TCF25, and MC1R as candidate genes were found to be possibly involved in the development of the black-headed coat color in sheep. Furthermore, we selected head coat color as a representative trait and performed an independent test of our GWAS findings through multiplex PCR SNP genotyping. The findings validated five mutation sites in chromosome 14 (14,251,947 T>A, 14,252,090 G>A, 14,252,158 C>T, 14,252,329 T>G, and 14,252,464 C>T) within the exon1 of the MC1R gene (517 bp), as identified by GWAS in an additional 102 Tan sheep individuals, and revealed that black-headed sheep predominantly exhibited heterozygous genotypes, possibly contributing to their color change. Our results provide a valuable foundation for further study of these three economically important traits, and enhance our understanding of genetic structure and variation in Chinese Tan sheep.